Physiological adaptation during short distance triathlon swimming and cycling sectors simulation - Gonzalez-Haro, C.; Gonzalez-de-Suso, J. M.; Padulles, J. M.; Drobnic, F.; Escanero, J. F. (Physiology & Behavior, 2005)
The aim of this study was to typify cardiorespiratory and metabolic adaptation capacity at race pace of high-level triathletes during simulations of short distance triathlon swimming sector, first transition and cycling sector. Six national and international-level triathletes performed a 1500 m swimming trial followed by a transition and one hour on ergocycle at race pace, with sequenced measures of blood lactate concentration, gas exchange and heart rate recording.